Internet censorship detected in Cambodia (Cambodia) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Cambodia. Data sourced from CensoredPlanet.
Censorship Incident ID: KH-2026-0084. Severity: warning. Confidence: 65%